Comparison of Outcomes and Complications Acetabular Reconstruction using an Antiprotrusio Cage and a Cemented Dual Mobility Cup or Simple Polyethylene Cup (Global Journal of Medical Research, 2014)
The current study evaluated the outcome of a retrospective series of 37 revision total hip arthroplasties with severe acetabular bone defects reconstruction using an antiprotrusio cage. We aimed to compare the peri and postoperative complications and mid-term outcomes of two groups, a reconstruction using a dual mobility cup (DMC) cemented into the cage (n=14) or a cemented simple polyethylene cup (SPEC) (n=23) at a mean follow-up of 5 years. We found an inverse association between the use of DMCs and both dislocation rate (p
Keywords: total hip arthroplasty; revision total hip arthroplasty; hip instability; hip dislocation; dual mobility cup; reinforcement cage device